IMPLEMENTASI METODE TEAM QUIZ DALAM MENINGKATKAN KEAKTIFAN PESERTA DIDIK KELAS VII PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMPN 31 BANDAR LAMPUNG - Devi Sela Eka Selvia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The learning process can be effective and efficient by planning the learning process, implementing the learning process, assessing learning outcomes, and monitoring the learning process. Therefore, every educational institution is obliged to organize an interactive, enjoyable, challenging, and motivating learning process for students to be active and creative. The use of appropriate learning methods can create learning conditions that allow students to learn actively. One interesting learning method is the team quiz method which is easy for students to understand and makes them happy and enthusiastic during the learning process. The aim of this research is to find out the planning, implementation, and evaluation of the team quiz method in Islamic religious education subjects for grade VII students at SMPN 31 Bandar Lampung.This study uses field research. The method used is descriptive qualitative, involving one teacher and grade VII students at SMPN 31 Bandar Lampung. Data collection techniques include observation, interviews, and documentation. The data were analyzed qualitatively using data reduction, data display, and conclusion drawing. The validity of the data was checked using source triangulation. The results of this study indicate that the implementation of the Team Quiz method in Islamic Religious Education subjects for grade VII students at SMPN 31 Bandar Lampung involves three stages: planning, implementation, and evaluation. In the planning stage, the teacher must prepare everything for the learning process; in the implementation stage, the teacher applies the method; and in the evaluation stage, the teacher assesses the entire learning process.